Role of nitric oxide on the replication of viral haemorrhagic septicemia virus (VHSV), a fish rhabdovirus - Tafalla, Carolina; Figueras Huerta, Antonio; Novoa, Beatriz (Veterinary Immunology and Immunopathology, 1999)
8 páginas, 2 figuras, 1 tabla In the present work, we have studied the role of nitric oxide (NO) on the replication of viral haemorrhagic septicemia virus (VHSV), a virus which produces high mortalities in fish aquaculture worldwide and that is known to replicate in turbot (Scophthalmus maximus) head kidney macrophages. Viral infection of turbot kidney macrophages in vitro induced an up-regulation of NO production and we have tested whether this endogenous NO production induced by VHSV on macrophages had an antiviral effect using the NO synthase inhibitor, N-!-nitro-L-arginine (LNAME). When L-NAME was added to the VHSV-infected cultures, no increase on VHSV titer was observed, eventhough the inhibitor was capable of decreasing NO production. When exogenous NO was apported by the nitric oxide donor, glycerin trinitrate (GTN) an antiviral effect on VHSV was observed. The NO donor significantly inhibited VHSV replication on a turbot fibroblast cell line (TV-1) and on turbot kidney macrophages. This research was supported by grant MAR 96-1775 from the Comision Interministerial de Ciencia y Tecnologia (CICYT). Peer reviewed